2017
DOI: 10.5152/tpa.2014.984
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the levels of knowledge and approaches in relation with child abuse and neglect in residents of pediatrics, pediatricians and practitioners working in the province of Ankara

Abstract: Aim: In this study, it was aimed to evaluate the levels of knowledge and approaches related with child abuse and neglect in pediatricians and practitioners who have a significant role in recognition and prevention of child abuse and neglect. Material and Methods:Two hundred residents of pediatrics and 100 pediatricians working in university and education and research hospitals in the center of Ankara province and 250 practicioners working in primary health care centers were included in the study. A scale compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…However, sex and specialty were not significantly associated with knowledge. A study in Turkey found similar results for age and work experience, but also found that female physicians had better knowledge than males (23).…”
Section: Discussionmentioning
confidence: 60%
“…However, sex and specialty were not significantly associated with knowledge. A study in Turkey found similar results for age and work experience, but also found that female physicians had better knowledge than males (23).…”
Section: Discussionmentioning
confidence: 60%
“…According to Swedish legislation (The Social Services Act, 2001), reporting is mandatory, even if child maltreatment is only suspected; something the nurses in the present study were well aware of. Nevertheless, under-reporting remains an issue in Sweden (Swedish Government Official Reports, 2009), as is the case in other countries (Kara et al, 2014; Lazenbatt and Freeman, 2006). In our study, the nurses described how they were sometimes concerned about submitting an unsubstantial report and how this would, in turn, affect the family.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that CHC nurses, in addition to general practitioners, under-report child maltreatment. This implies that children are not receiving the protection they require (Kara et al, 2014; Lazenbatt and Freeman, 2006). Different reasons for under-reporting have been discussed and include, for example, lack of knowledge and ignorance of the reporting process (Borres and Hagg, 2007; Gilbert et al, 2009a; Kara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers performed studies using the Scale Form for Identifying the Symptoms and Risks of Child Abuse and Neglect. Demir [23] in physicians, Kocaer [24] in nurses and physicians, Kara [25] in physicians and Yılmaz [26] in nurses as study groups. Corroborating, those studies have shown that those who do not have children scored higher in the scale.…”
Section: Discussionmentioning
confidence: 99%